2020
DOI: 10.1021/acs.iecr.0c02618
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient MXene-Coated Flame Retardant Cotton Fabric for Electromagnetic Interference Shielding

Abstract: In this work, a highly efficient flame retardant and electromagnetic interference (EMI) shielding coating on cotton fabric was fabricated by a simple solution impregnation and dipcoating method, which involved three layers of polyacetimidate (PEI), ammonium polyphosphate (APP), and Ti 3 C 2 T x . When exposed directly to flame, the PEI/APP coating lead to a char layer resulting in self-extinguishing performance. Particularly, the cotton fabric coated by increasing amounts of Ti 3 C 2 T x gradually achieved EMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 53 publications
0
52
0
Order By: Relevance
“…Zhang et al reported that the Ti 3 C 2 T x modified fabric with a low Ti 3 C 2 T x loading 6 wt% exhibited excellent electrical conductivity of 5 Ω sq −1 and outstanding EMI shielding performance (up to 36 dB) [ 111 ]. Cheng et al fabricated a Ti 3 C 2 T x MXene-coated cotton fabric by a simple solution impregnation and dip-coating method [ 112 ]. The cotton fabric coated by rising amount of Ti 3 C 2 T x could improve the EMI shielding performance.…”
Section: Mxene-based Materials For Emi Shieldingmentioning
confidence: 99%
“…Zhang et al reported that the Ti 3 C 2 T x modified fabric with a low Ti 3 C 2 T x loading 6 wt% exhibited excellent electrical conductivity of 5 Ω sq −1 and outstanding EMI shielding performance (up to 36 dB) [ 111 ]. Cheng et al fabricated a Ti 3 C 2 T x MXene-coated cotton fabric by a simple solution impregnation and dip-coating method [ 112 ]. The cotton fabric coated by rising amount of Ti 3 C 2 T x could improve the EMI shielding performance.…”
Section: Mxene-based Materials For Emi Shieldingmentioning
confidence: 99%
“…Polyimide (PI) aerogels (PIA) have garnered exceeding interest due to their low density and exceptional thermal stability. Hence, 2-D M-X/PIA nanoarchitecture has been fabricated and demonstrated interesting F-R behavior (Cheng et al 2020).…”
Section: Influence Of Catalysismentioning
confidence: 99%
“…M-X, similar to graphene has displayed prospects of being utilized in F-R polymeric matrice (Cheng et al 2020). Nevertheless, the fabrication of F-R M-X polymeric nanoarchitecture has been obstructed as a result of M-X inferior interfacial compliance with the polymeric matrix.…”
Section: Influence Of Catalysismentioning
confidence: 99%
“…To meet safety regulations and expand the use of cotton in textile applications, a signi cant number of surface treatment approaches have been developed for improving the protection performance by enhancing the ame retardant and antimicrobial properties of the CFs (Li et al 2019a(Li et al , 2020Liu et al 2020; Pan et al 2015;Xue et al 2020). Along with a remarkable improvement in quality of life and evergrowing consumer demands, there have been dramatic increases in the developing of functional fabrics, especially as protective functional textiles (e.g., electromagnetic interference shielding (Cheng et al 2020; Wang et al 2019;Zhang et al 2019), antistatic (An et al 2020), and UV-protection (Hu et al 2015) and healthcare textiles (e.g., antimicrobial activity (Fang et al 2015;Sa et al 2020) and far-infrared emission (Hu et al 2015). Many complex applications require multifunctional fabrics, generally by integrating the ame retardant, antistatic and antibacterial properties (An et Although the eld of surface treatment of the CFs has made great progress, to date, it is still a technical challenge to fabricate durable multifunction and maintain simultaneously their pristine performances.…”
Section: Introductionmentioning
confidence: 99%